Effect of Stroke Unit Nursing Mode on the Prognosis of Patients with Ischemic Stroke - Limin ZHANG; Dong PANG (康复学报)
Objective:To observe the effect of stroke unit nursing on the prognosis of patients with ischemic stroke.Methods:A total of 216 patients with ischemic stroke which were treated in the first affiliated hospital of Harbin Medical University were randomly divided to the control group and observation group, with 108 patients in each group. The control group was given neurology department symptomatic treatment and routine neurological rehabilitation nursing, such as health education, psychological guidance, early limb rehabilitation training, etc.the continuous intervention was for one month. The observation group was given stroke unit nursing mode, continuous intervention for one month. After admission, a professional stroke unit nursing team was established to scientifically formulate individual rehabilitation programs, including the following aspects:①To evaluate the patients'condition scientifically and provide corresponding nutrition support.②To carry out health education when the patients'condition is stable, such as lectures on stroke knowledge, guidance on the prevention of falls and aspiration, and so on.③To carry out targeted psychological counseling.④To carry out personalized rehabilitation programs such as limb rehabilitation, swallowing rehabilitation, respiratory rehabilitation training and traditional Chinese medicine physical therapy, and strengthen discharge follow-up. Serum visfatin, adiponectin, triglyceride and total cholesterol levels were measured before intervention and one month after intervention. NIH stroke scale (NIHSS) was used to evaluate neurological deficit, Fugl-Meyer assessment (FML) was used to assess limb motor function, modified Barthel index (MBI) was used to assess daily living ability, Hamilton depression scale (HAMD) was used to assess depression status, and clinical outcomes, complication rates and patient satisfaction with care were recorded.Results:Before intervention, there was no significant difference in the levels of visfatin, adiponectin, triglyceride, total cholesterol and the scores of NIHSS, FMA, HAMD, MBI of both groups (P>0.05). Compared with before intervention, after intervention for one month, the levels of visfatin, triglyceride, total cholesterol and the scores of NIHSS and HAMD of both groups were significantly lower, adiponectin level, FMA and MBI scores were higher, with statistical significance (P<0.05). Compared with the control group, after intervention for one month, the levels of visfatin, triglyceride, total cholesterol and the scores of NIHSS and HAMD of the observation group were significantly lower, adiponectin level, FMA and MBI scores were higher, with statistical significance (P<0.05). The excellent prognosis rate (94.44%) and nursing satisfaction rate (98.15%) in the observation group were higher than those of the control group (75.00%,80.56%), and the complication rate (7.41%) was lower than that of the control group (38.89%) (P<0.05).Conclusion:Stroke unit nursing mode is helpful to improve the blood lipid levels of patients with ischemic stroke, promote the recovery of nerve damage and limb motor function, improve psychological depression, reduce complications and improve clinical outcomes.